LICEO RURAL SANTA TERESA: PRESERVING THE HABITAT AND LOCAL CULTURE (Biocenosis, 2014)
This article shows the experience in the Liceo Rural de Santa Teresa, where students of this school were involved in a number of activities, making them actors and architects of their own history and that of the towns to which they belong. Among the activities were the development of a mural, the application of a questionnaire to identify the main environmental problems of the area and the implementation of an environmental workshop. It was possible that students actively participate and develop some actions that demonstrate their commitment.
Keywords: Coastal rural community; Environmental analysis and diagnosis; Citizen participation